AN ANALYSIS OF ERRORS IN OFFICIAL LETTER WRITING AT THE KAMPUNG BARU VILLAGE OFFICE IN 2025 - Dini Thiyana Luthfi; Alber (JURNAL KONFIKS, 2026)
This study aims to identify and describe errors in official letter writing at the Kampung Baru Village Office in 2025 and analyze the various factors behind the occurrence of these errors. This study uses a descriptive qualitative approach with a content analysis method. The data source in this study is an archive of official letters sourced from 50 outgoing letters at the Kampung Baru Village Office in 2025. The data in this study are errors in outgoing letter writing at the Kampung Baru Village Office. All data were obtained through documentation and interview techniques, then analyzed referring to the theory of language errors in official letters. The results showed that there were 237 error data based on nine categories of letter writing. Language errors in the letter content were the most dominant finding with a frequency of 57 data. Other significant errors were found in the writing of letter numbers (36 data) and letter addresses (35 data). Specifically, errors in the letter content include errors in the use of capital letters, sentence structure, common abbreviations, writing rupiah nominals, writing colons (:), writing the suffix -nya, to the format for writing NIP and the name of the signatory that does not comply with the latest rules. The factors causing these errors include communication barriers in understanding instructions from higher-level agencies, overlapping workloads (multitasking), the lack of a specific guidebook for official scripts in the village office, and inaccuracy in the choice of diction. Based on the research results, it can be concluded that the quality of correspondence at the Kampung Baru Village Office still requires significant improvement through the provision of applicable technical guidelines and the implementation of regular technical guidance training for village officials.